Molecular genetic characterization of a prenatally detected de novo interstitial deletion of chromosome 2q (2q31.1-q32.1) encompassing HOXD13, ZNF385B and ZNF804A associated with syndactyly and increased first-trimester nuchal translucency - Chih-Ping Chen; Chen-Ju Lin; Yen-Ni Chen; Schu-Rern Chern; Shin-Wen Chen; Shih-Ting Lai; Peih-Shan Wu; Li-Feng Chen; Wayseen Wang (Elsevier, 2017)
Objective: We present prenatal diagnosis and molecular genetic characterization of a de novo interstitial deletion of 2q (2q31.1-q32.1) and discuss the genotype-phenotype correlation. Case report: A 34-year-old, primigravid woman was referred to the hospital at 20 weeks of gestation for genetic counseling because of a prenatally detected de novo interstitial deletion of chromosome 2q (2q31.1-q32.1). She underwent amniocentesis at 17 weeks of gestation because of advanced maternal age and an increased first-trimester nuchal translucency (NT) thickness of 3.6 mm. Amniocentesis revealed a karyotype of 46,XY. However, array comparative genomic hybridization (aCGH) analysis on the DNA extracted from uncultured amniotic fluid and amniocytes revealed a 13.29-Mb deletion at chromosome 2q31.3-q32.1. The parents did not have such a deletion. Prenatal ultrasound findings were unremarkable. After counseling of the genotype-phenotype correlation of such a chromosome aberration with congenital malformations, the parents elected to terminate the pregnancy. The fetus postnataly manifested hypertelorism and syndactyly of the second and third toes of bilateral feet. Cytogenetic analysis of the umbilical cord revealed a karyotype of 46,XY,del(2)(q31q32). aCGH analysis on the DNA extracted from the cord blood confirmed a 13.35-Mb deletion of 2q31.1-q32.1 encompassing HOXD13, ZNF385B, ITGA4, CERKL, PDE1A, FRZB and ZNF804A. Polymorphic DNA marker analysis revealed a paternal origin of the deletion. Conclusion: Fetuses with an interstitial deletion of 2q31.1-q32.1 may be associated with increased first-trimester NT. Haploinsufficiency of HOXD13 is associated with syndactyly. Genomic microarray is useful in detecting subtle chromosomal abnormalities in fetuses with increased NT and normal karyotype.